Enterococcus faecalis Septicemia and Vertebral Osteomyelitis after Transrectal Ultrasound Guided Biopsy of the Prostate - Ayaz Virji; Lucio R. Minces; Zargham Abbass (Case Reports in Infectious Diseases)
Transrectal ultrasound guided prostate biopsy (TRUS) has rarely been associated with disseminated infection, yet the occurrence appears to be increasing. Resistance to fluoroquinolones, the most commonly used prophylaxis, is one of the likely causes, with Escherichia coli being the most commonly reported cause of these infections. Herein we present what is, to our knowledge, the first case of Enterococcus faecalis septicemia and vertebral osteomyelitis after TRUS. Previously reported cases of this condition are referenced also.